Strategic Capability Alignment and Cooperative Performance: A Conceptual Management Perspective from Indonesia - Fahmi, Indra; Farida, Farida (Jurnal Minds: Manajemen Ide dan Inspirasi, 2025)
Cooperatives increasingly face pressure to remain competitive while balancing entrepreneurial adaptation and governance stability in rapidly transforming economic environments. This study contributes by developing a Strategic Capability Alignment Model that reconceptualizes cooperative performance as an outcome of the alignment between Entrepreneurial Orientation and Managerial Capability, with innovation functioning as the integrative mechanism connecting adaptive and stabilizing capabilities. Rather than testing causal relationships empirically, the study employs a conceptual model development approach through analytical synthesis of peer-reviewed studies, institutional reports, and cooperative management literature published between 2014 and 2024 within the Indonesian cooperative context. The analysis demonstrates that cooperative sustainability and organizational transformation depend not on isolated managerial attributes but on the strategic alignment of complementary capabilities within governance systems. The study implies that cooperative leaders should design governance-oriented innovation strategies that simultaneously strengthen entrepreneurial adaptability and managerial stability.